The Structure-Culture Alignment Activity: Aligning Organizational Structure Elements With Diversity, Equity, and Inclusion Cultural Values - Wyland, Rebecca; Hanson-Rasmussen, Nancy; Clark, Frazier (Journal of management education, 2024)
The purpose of this article is to present an instructional innovation called the Structure-Culture Alignment Activity, which leads students through the process of aligning cultural values pertaining to diversity, equity, and inclusiveness (DEI) to two important structural elements, formalization and centralization. Using decision making, team cooperation, reflection of preferences, and practice in decision-making skills, students create a part of a strategic plan for a new organization. In this article, we offer detailed instructions, learning objectives, debrief questions, extensions, and variations for the Structure-Culture Alignment Activity. We also offer our suggestions from lived experience in running the Structure-Culture Alignment Activity as well as the findings from our statistical analysis. Our findings contribute to management education literature and suggest that participation in the Structure-Culture Alignment Activity improves knowledge pertaining to structural elements, diversity value attitudes, and attitudes towards aligning organizational structural elements with DEI cultural values in an undergraduate management class.